Chinese Herbal Medicine Industry Development: A Study on the Rural Revitalization Strategies of Huaihua City in Central China - Xiaoqing, Wei; Jia, Chen; Bingjia, Chai; Guang, Tian (Journal of Marketing Development and Competitiveness, 2022)
The prosperity of industries is the primary task of rural revitalization. Nowadays, the development of the Chinese herbal medicine industry has been included in the state’s rural revitalization strategy, and the authentic herbal medicine industry in Huaihua City has ushered in new development opportunities. The quality of Chinese herbal medicine in Huaihua City is high, indicating a vast potential for industrial development. However, such problems are low brand influence and a weak industrial foundation. By adopting the methods of literature review and SWOT analysis, this paper sorts out the frontier research findings of industrial prosperity and the development of the Chinese herbal medicine industry and analyzes the status of the Chinese herbal medicine industry in Huaihua City in Central China. It proposes countermeasures to enhance the brand building and promote industrial integration. The development model of Huaihua’s characteristic herbal medicine industry explores a new path for rural revitalization and provides rural revitalization solutions for Central China.